Alginate biopolymer as a reactor container for copper oxide-tin oxide: Efficient nanocatalyst for reduction of different pollutants. (March 2022) - Khan, Sher Bahadar; Akhtar, Kalsoom; Bakhsh, Esraa M.; Kamal, Tahseen; Asiri, Abdullah M.
Abstract: The need of clean water demands to design an efficient catalytic system with high effective and selective reduction of water pollutants. Here, we successfully prepared copper oxide-tin oxide (CuO–SnO2 ) nanomaterial and further wrapped in Na-alginate hydrogel (Alg/CuO–SnO2 ). CuO–SnO2 and Alg/CuO–SnO2 were characterized by FESEM, EDS, FTIR-ATR, and XRD and tested for the reduction of water pollutants. The catalytic ability of CuO–SnO2 and Alg/CuO–SnO2 was examined for numerous pollutants like 4-nitrophenol (4-NP), methyl orange (MO), congo red (CR), methylene blue (MB) and potassium ferricyanide (K3 [Fe(CN)6 ]) where the designed CuO–SnO2 and Alg/CuO–SnO2 nanocatalysts were most selective toward MB reduction. Further on optimization of catalyst amount, stability, and reducing agent amount, it was found that the increase of nanocatalyst amount and NaBH4 concentration increase the rate of MB reduction. CuO–SnO2 and Alg/CuO–SnO2 nanocatalysts reduced MB in 3.0 min with reaction rate constants (k app ) of 1.2944 min −1 and 1.2715 min −1, respectively. Additionally, Alg/CuO–SnO2 nanocatalyst was easily recovered by simply pulling hydrogel after completion of reaction and reused four times with no loss in efficiency. Besides, Alg/CuO–SnO2 nanocatalyst was further investigated in real samples like sea water, irrigation water, well water, university wastewater and found effective for MB reduction even in real samples. Graphical abstract: Image 1 Highlights: Efficient nanocatalyst based on CuO–SnO2 and Alg/CuO–SnO2 . Utilization of nanocatalysts for reduction of organic and inorganic pollutants. High rate constants of CuO–SnO2 (1.2944 min −1 ) and Alg/CuO–SnO2 (1.2715 min −1 ). Optimization of NaBH4 amount, selectivity, and dosage of Alg/CuO–SnO2 . Highly stable and recyclable catalyst without loss in activity up to four cycles.